Mechanical and durability assessments of steel slag-seashell powder-based geopolymer concrete - Wilson Okoro; Solomon Oyebisi (Heliyon, 2023)
Globally, an increasing carbon footprint has had a negative effect on the ecosystem and all living things. One of the sources that produces these footprints is the cement manufacturing process. Therefore, it is crucial to produce a cement substitute to reduce these footprints. The production of a geopolymer binder (GPB) is one of these possibilities. In this study, sodium silicate (Na2SiO3) was used as an activator in the production of geopolymer concrete (GPC) together with steel slag and oyster seashell as precursors. The materials of the concrete were prepared, cured, and tested. Workability, mechanical, durability and characterization test were conducted on the GPC. The results showed that adding a seashell increased the slump value. The optimum GPC compressive strength on a 100 × 100 × 100 mm3 cube for 3, 7, 14, 28, and 56 curing days was obtained with 10% seashell, while seashell replacement exceeded 10% declined in strength. Portland cement concrete achieved better mechanical strength when compared to steel slag seashell powder geopolymer concrete. However, steel slag seashell powder-based geopolymer gained better thermal properties than Portland cement concrete at 20% seashell replacement.